Airflow limitation and survival after surgery for non-small cell lung cancer: Results from a systematic review and lung cancer screening trial (NLST-ACRIN sub-study). (September 2019) - Hopkins, R.J.; Ko, J.; Gamble, G.D.; Young, R.P.
Highlights: Smokers with chronic obstructive pulmonary disease (COPD) have higher rates of lung cancer. Their outcomes following surgery for early stage lung cancer, remains unclear. We used a meta-analytic approach and results from the National Lung Screening Trial to examine this issue. Following surgery, 5-year survival is similar in those with and without spirometry defined COPD. However, the presence of COPD may influence the decision not to undergo surgery. Abstract: Objective: Lung cancer remains the single greatest cause of cancer mortality where surgery for early stage non-small cell lung cancer achieves the greatest survival. While there is growing optimism for better outcomes with screening using annual computed tomography, the impact of co-existing airflow limitation on survival remains unknown. To compare survival in non-small cell lung cancer patients undergoing surgery stratified according to the presence or absence of pre-surgery airflow limitation. Materials and Methods: We undertook a systematic literature search of non-screen lung cancer that encompassed studies reported between January 1946 and January 2017. Full-text articles were identified following eligibility scoring, with data extracted and analysed using a standardised analytical method (PRISMA). The results of this systematic review in non-screen lung cancers were compared to real-world results from a lung cancer screening cohort (N = 10, 054), where outcomes following surgery could be compared after stratification according to pre-surgery airflow limitation. Results: In the systematic review, 6899 subjects were included from 10 studies; 7 were retrospective, 3 were prospective. Overall survival was 950 (44%) in 2144 people with COPD and 2597 (55%) from 4755 controls (unadjusted P value <0.001). However, the overall meta-analysed random effects odds ratio for overall survival (N = 10) and 5-year survival (N = 4) comparing those with and without COPD was 0.91 (95% CI = 0.84–1.00) and 0.99 (95% CI = 0.79–1.24) respectively. There were no signs of significant heterogeneity (I 2 = 19.1%, P = 0.27) nor publication bias as assessed by funnel plot and Egger's test (P = 0.19). In the lung cancer screening sub-study of 10, 054 screening participants we found no difference in 5-year survival in those with and without airflow limitation (84% and 81% respectively, P = 0.64). Conclusion: Survival after surgery for non-small cell lung cancer is comparable between those with and without spirometry evidence of airflow limitation. This finding was replicated in lung cancer diagnosed during screening.